2003
DOI: 10.1183/09031936.03.00292203
|View full text |Cite
|
Sign up to set email alerts
|

Increased ventilation with NiIPPV does not necessarily improve exercise capacity in COPD

Abstract: Increased ventilation with NiIPPV does not necessarily improve exercise capacity in COPD. M.P. Highcock, J.M. Shneerson, I.E. Smith. #ERS Journals Ltd 2003. ABSTRACT: Evidence that noninvasive intermittent positive-pressure ventilation (NiIPPV) improves exercise capacity in chronic obstructive pulmonary disease (COPD) is limited. The effectiveness of different ventilators in this setting has not been studied.Three bilevel pressure support ventilators (Bipap S/T 30, Nippy2 and Vpap II ST), applied via a mouthpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
2
17
0
2
Order By: Relevance
“…All prior studies evaluating NIV assessed exercise tolerance via the 6-min walk test or shuttle walk test and showed no improvement in the NIV groups, 18,19,[24][25][26] in agreement with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…All prior studies evaluating NIV assessed exercise tolerance via the 6-min walk test or shuttle walk test and showed no improvement in the NIV groups, 18,19,[24][25][26] in agreement with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…6). Combined data for four studies [17,18,25,26] showed an increase in VT/tI (p50.02); however, heterogeneity was evident (p50.45; [26,27] showed an increase in respiratory muscle strength with bilevel NIPPV, although heterogeneity was evident (table 9 and fig. 9).…”
Section: Lung Functionmentioning
confidence: 98%
“…Meta-analysis of five non-RCTs [17,18,[26][27] that assessed ventilatory/breathing pattern parameters with bilevel NIPPV showed an increase in VT (MD 195.64 mL, 95% CI 21.97-369.31 mL; p50.03; table 6 and fig. 6).…”
Section: Lung Functionmentioning
confidence: 99%
See 2 more Smart Citations